Preventive decompressive craniectomy for ruptured cerebral aneurysm in the first trimester of pregnancy: successful outcome for mother and fetus - Mikhail E. Pershin; Dmitry V. Litvinenko; Tatyana I. Konareva; Vyacheslav V. Tkachev (Сеченовский вестник)
One of the ways to improve functional outcomes in patients with ruptured cerebral aneurysms is preventive decompressive craniectomy (DC). Such tactics have not been studied during pregnancy.Case report. A 34-year-old female patient, who was 10 weeks pregnant, was hospitalized for an acute headache. According to imaging methods, rupture of the aneurysm of the right internal carotid artery (ICA), subarachnoid parenchymal subdural hemorrhage, pronounced widespread arteriospasm were diagnosed. Consent to surgical treatment with the condition of prolongation of pregnancy was obtained only on the 4th day of the disease against the background of an increase in the volume of subdural hematoma and displacement of median structures. DC was performed and the aneurysm was clipped. The course of the postoperative period was favorable. At 40 weeks of pregnancy, a cesarean section delivery was performed, the child is healthy. Subsequently, cranioplasty of the skull bone defect was performed.Discussion. The first case of successful treatment of a patient with a ruptured ICA aneurysm in the first trimester of pregnancy using DC is presented. The treatment of pregnant women with ruptured cerebral aneurysms in the first trimester of pregnancy presents significant difficulties in medical, moral, ethical and legal terms. A multidisciplinary approach, a balanced assessment of the severity of the disease and pregnancy, individual risks of surgery and potential complications, the volume of diagnostic procedures and intensive care measures performed, make it possible to preserve the life and health of the mother and fetus.